The influence of motivation on presenteeism behaviour / Nur Ain Syuhada Mohd Noor - Mohd Noor, Nur Ain Syuhada (2018)
Productivity level in the country has been declining in the past few years. It is caused by the low quality of work performed by the employees. Low work quality is said to be resulted from presenteeism as one of the reasons. Presenteeism has become a prevalent issue in today‘s world where the employees come to work despites of being sick. When employees are motivated, they will have the tendency to engage in presenteeism which it is impactful in determining Malaysia‘s productivity as a whole. Therefore, the purpose of this study is to identify the influence of motivation on presenteeism behaviour. Subsequent to this, the moderating effect of job satisfaction on the relationship between motivation and presenteeism also was investigated. Through a quantitative design, a cross-sectional survey using questionnaires was employed. Identifying the units of analysis was through stratified and convenience sampling methods to collect the data. Also, the focus of this study is limited to employees working in Hospital Tuanku Ampuan Najihah, Kuala Pilah. From a sample size of 300 (n=300), the returned rate was 287 or 95.67%. There is a significant relationship between the need for power under motivation dimension and level of presenteeism where the significant value of p is less than 0.05. This study also found the significant moderating role of job satisfaction under the dimension of satisfaction towards contribution on the relationship between need for power and presenteeism. This study helps in contributing clear knowledge in terms of organizational behaviour and academic by highlighting the role of motivation in influencing the behaviour of an employee where in this case it is presenteeism which may impact the country‘s productivity.